Redox Mediators for Li2CO3 Decomposition - Zixuan Liu; Haoshen Huang; Zhengfei Chen; Haiyong He; Deyu Wang; Zhoupeng Li (Inorganics)
Lithium–air batteries (LABs) possess the highest energy density among all energy storage systems, and have drawn widespread interest in academia and industry. However, many arduous challenges are still to be conquered, one of them is Li2CO3, which is a ubiquitous product in LABs. It is inevitably produced but difficult to decompose; therefore, Li2CO3 is perceived as the “Achilles’ heel of LABs”. Among various approaches to addressing the Li2CO3 issue, developing Li2CO3-decomposing redox mediators (RMs) is one of the most convenient and versatile, because they can be electrochemically oxidized at the gas cathode surface, then they diffuse to the solid-state products and chemically oxidize them, recovering the RMs to a pristine state and avoiding solid-state catalysts’ contact instability with Li2CO3. Furthermore, because of their function mechanism, they can double as catalysts for Li2O2/LiOH decomposition, which are needed in LABs/LOBs anyway regardless of Li2CO3 incorporation due to the sluggish kinetics of oxygen reduction/evolution reactions. This review summarizes the progress in Li2CO3-decomposing RMs, including halides, metal–chelate complexes, and metal-free organic compounds. The insights into and discrepancies in the mechanisms of Li2CO3 decomposition and corresponding catalysis processes are also discussed.